Youth Generation Moral Education in Muhammadiyah University of Enrekang - Saldi Saldi; Selfie Ulansari; Rahmahdhani . J.N; Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2022)
Morals are good behavior that appears from a person after carrying out Islamic law, so that these morals and customs are formed into behaviors and traits that are firmly embedded in the self, so that when carrying out an act without requiring prior consideration. Morals occupy a special position in Islam, namely they are positioned together with the essence of ihsan, so that aqidah and shari'a will not be perfect without morals because all three are an inseparable unit. So the higher a person's Iman, the better his morals. One of the factors of moral decline is caused by internal factors, namely "the loss of adab" the loss of adab in the form of loss of body, mind and soul discipline caused by the influences of westernization that are not in accordance with Islamic law. Therefore it is necessary to re-instill moral values in various ways such as: (1) habituation to children in good behavior, (2) exemplary parents and teachers, (3) always giving good advice to children, and (4) tell stories of wisdom so that children can take life lessons from these stories.